Cerebral venous sinus thrombosis with heterozygous methylenetetrahydrofolate reductase mutation: Cause or chance association? - Prabir Maji; Sudhir Mishra; Deepshikha Singh (Wolters Kluwer Medknow Publications, 2021)
Background: Cerebral venous sinus thrombosis (CSVT) in children is a rare, obscure, but potentially fatal problem. The clinical presentation is varied, as is the multiple underlying causes. CSVT can be seen in patients with inherited or acquired prothrombotic risk factors, even in the absence of an underlying condition. The respective etiological roles of methylenetetrahydrofolate reductase (MTHFR) CG677T mutation and hyperhomocysteinemia in CSVT is still not clear. We present a case of CSVT following a minor head injury, in whom an MTHFR mutation was identified, but with initial normal homocysteine levels. Clinical Description: A 9-year-old boy presented with nonaccidental fall followed by persistent headache, projectile vomiting, bradycardia and hypertension suggesting features of raised intracranial pressure. Brain imaging (magnetic resonance venography) showed extensive dural venous sinus thrombosis. Prothrombotic workup revealed heterozygous CG677T polymorphism of the MTHFR gene with normal serum homocysteine, B12 and folate levels. Management: The child was given supportive management. Low-molecular-weight heparin was initiated followed by long-term warfarin. There were no neurological deficits at discharge. Six months afterward, there is persistence of thrombosis with partial recanalization in the affected cerebral sinuses. The serum homocysteine level is now marginally elevated. Conclusion: Available neuroimaging should be promptly instituted to establish CSVT. A targeted search for prothombotic risk factors should be undertaken but within the proper timeframe. Genetic mutations may be identified accurately in the acute phase, but other factors should be done after 4-6 weeks. The relationship between MTHFR polymorphisms and hyperhomocysteinemia with venous thrombosis is yet to be defined.